Comparing direct oral anticoagulants versus vitamin K antagonist in patients with atrial fibrillation after transcatheter aortic valve replacement: an updated meta-analysis. (3rd October 2022) - Dhaliwal, A; Kaur, A; Konje, S; Bhatia, K; Sohal, S; Rawal, H; Turagam, M; Gwon, Y; Mamas, M; Dominguez, A; Bhatt, D; Velagapudi, P
Abstract: Background: Oral anticoagulation therapy is indicated for patients undergoing transcatheter aortic valve replacement (TAVR) with concomitant or new onset atrial fibrillation (AF). However the data on optimal anticoagulation regimen in this population remains unclear. Purpose: To compare efficacy and safety outcomes of direct oral anticoagulants (DOACs) versus Vitamin K antagonists (VKA) in patients with AF post TAVR. Methods: We searched electronic databases (PubMed, Embase, Scopus, Cochrane) from inception to February28th, 2022 using MeSH terms and keywords for DOACs, AF or TAVR. Primary outcome of interest was all-cause stroke or systemic embolic event. Secondary safety outcomes were major bleeding and all-cause mortality. Pooled risk ratio (RR) and 95% confidence interval (CI) were calculated using a random-effects model. Interstudy heterogeneity was assessed using the Higgins I 2 value. All statistical analysis were performed using RevMan 5.4.1 software. Results: We identified five eligible studies (1RCT, 4 observational) including 3694 patients (DOAC n=1581, VKA n=2113). The mean age was 81.4±0.9 years. The mean follow-up was 12.4±14.3 months. Type of DOACs included apixaban (n=394, 24.9%), rivaroxaban (n=354, 22.4%), dabigatran (n=119, 7.5%) and edoxaban (n=714, 45.2%).There was no significant difference in primary outcome of stroke or systemic embolic event (RR: 0.93; CI: 0.65–1.33; p>0.05; I 2 =5%), or in secondary outcomes of major bleeding (RR: 1.02; CI: 0.78–1.34; p>0.05; I 2 =44%) and all-cause mortality (RR: 0.87; CI: 0.59–1.27; p>0.05; I 2 =56%) between DOACs and VKA groups. Conclusion: This meta-analysis shows anticoagulation therapy with DOACs has similar safety and efficacy outcomes compared to VKA in patients with AF undergoing TAVR. Funding Acknowledgement: Type of funding sources: None.